Species Composition of Leaf Footed Bugs (Coreidae: Hemiptera) in Hilly Regions of Nepal - KC, S.; Kafle, K.; Khadka, A. (Journal of the Institute of Agriculture and Animal Science, 2018)
A survey of leaf footed bugs (Hemiptera: Coreidae) was conducted in two hilly districts of Nepal viz. Lamjung and Kaski, over a period of 13 months (April 2017-May 2018). The prime purpose of the research was to find out the Coreidae diversity in these regions which hasn’t been done before. Sundarbazar, Kunchha and Dura Daanda areas from Lamjung and Hemja and Sarangkot from Kaski were explored. A total of 111 specimens of Coreidae were collected from altitude varying from 700-1600 masl. Eleven different species of these bugs from 1 subfamily, 7 tribes and 7 genera were recorded. All the species fell under single subfamily Coreinae Leach, 1815. One species, Acanthocoris scabrator (Fabricius, 1803) fell under the tribe Acanthocorini Bergroth, one species, Leptoglossus gonagra (Fabricius, 1775) fell under tribe Anisoscelini Laporte, one, Cloresmus khasianus (Distant, 1901) under Cloresmini (Stal) and one, Dalader acuticosta (Amyot & Serville, 1843) under Daladerini Stal. Similarly, 3 species viz. Cletus bipunctatus (Herrich-Schäffer, 1840), Cletus pygophorus (Gupta & Singh, 2013) and Cletus trigonus (Thunberg, 1783) fell under the tribe Gonocerini Mulsant and Rey. Likewise, 3 species were found under the tribe Homoeocerini Amyot and Serville viz. Homoeocerus (Anacanthocoris) striicornis (Scott, 1874), Homoeocerus (Anacanthocoris) sp. and Homoeocerus (Tliponius) unipunctatus (Thunberg, 1783) and 1 species, Anoplocnemis phasianus (Fabricius, 1781) was found under Mictini Amyot and Serville.